Historical-Geographical Features of Tourism Development in Russia - SHULGINA, Daria Pavlovna; SHULGINA, Olga Vladimirovna (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019, 2019)
The article looks at the main historical periods of tourism development in Russia and the geographical pattern of its expansion across the territory of the country. Historical-geographical features of tourism development in the pre-Revolutionary, Soviet and post-Soviet periods have been identified. Based on archival, literary, statistical and map data sources, the article provides spatiotemporal characteristics of each stage of tourism development in Russia: consumers of travel services and their numbers, main objects of cultural heritage as tourist resources; tourist infrastructure, information support of tourism (published guidebooks, reference books, maps, postcards, and Internet resources).